A Literature Review of the Measurement of Coping with Stigmatization and Discrimination. Issue 5 (3rd September 2021) - Partow, Sara; Cook, Roger; McDonald, Rachael
Abstract: Research suggests there is a link between stigma-related stress and the mental health of the stigmatized, with coping being recognized as an important mediator/moderator of this relationship. Standardized questionnaires have been commonly used to measure coping in this body of research. This article identifies some of these studies and discusses several of these instruments, with a focus on their appropriateness for studying coping with stigmatization and discrimination. A systematic search of the literature was adapted for this review. The search term "(cope OR coping) AND stress* AND (stigma OR discriminat*)" was used, within the abstract field of five scientific databases. Articles that then met certain inclusion criteria were reviewed and organized using a matrix approach. Race and ethnicity were the most frequent stigma characteristics studied, with some commonly stigmatized groups being absent from the literature. Measures specifically designed to assess coping with stigmatization or discrimination were used less frequently. Only a few studies measured coping responses related to a specific form of stigmatization or discrimination.